Effect of Green Papaya Fruit Vegetable Consumption On Increasing Breast Milk Production in Breastfeeding Mothers in Caile Health Center - Hasrini; Tenriwati; Asnidar (Jurnal Life Birth, 2021)
The background is that breast milk is the best food for a baby in the first 6 months of life. All nutritional needs such as protein, carbohydrates, fats, vitamins, and minerals are well met from breast milk. There are various factors that can increase the production of breast milk, one of which is by increasing the intake of lactogogum contained in papaya butah. Lacktogogum sitesis is not widely known and relatively expensive so it is necessary to find alternative drugs. Papaya fruit is a fruit that contains lactogogum known as tropical fruit, papaya fruit or Carica papaya is also one type of fruit that has nutritional content and is rich in health benefits. The purpose of this study is to find out the effect of green papaya fruit consumption on increasing breast milk production in breastfeeding mothers. The research method used is the Pre Experiment method with the design of one group pre test and post test design without the use of comparison groups (controls). The results of the study can be seen that the production of breast milk before the consumption of papaya vegetables the average frequency of breastfeeding is 8.7 times and after consuming papaya fruit vegetables increased to 12.95 times with a value of t count = 7,701 greater than the value of t table = 1.74 (t count > t table) with Sig 0.000. Because Sig < 0.05, it means that the average milk production before and after papaya consumption is different. The conclusion is that there is an effect on the consumption of green papaya fruit vegetables on the increase in breast milk production in nursing mothers in Caile Health Center.